Local walkability index: assessing built environment influence on walking - Reisi Marzieh; Nadoushan Mozhgan Ahmadi; Aye Lu (Bulletin of Geography. Socio-Economic Series)
Walking is a more sustainable transport mode, and governments around the world are trying to deliver highly walkable areas to their people. Due to its importance, walkability has been a research topic in recent years. Vast empirical studies have reported evidence related to the influence of built environment on walking as a major physical activity. Considering the recent literature, this study developed a framework to quantify walkability by applying a set of indicators related to built environment. The indicators were normalised, weighted and integrated into an overall walkability index. The research was conducted on Chaharbagh Street, which is a major and ancient street in the Isfahan metropolitan area, Iran. The proposed framework would be helpful in investigations of whether a specific area is an appropriate option for a car-free plan based on its built environment features. The outcome of the study could be applied to understand issues related to pedestrian infrastructure and to propose corrective actions.